Degradation Behavior of Scalable Nonfullerene Organic Solar Cells Assessed by Outdoor and Indoor ISOS Stability Protocols. Issue 12 (24th June 2020) - Greenbank, William; Djeddaoui, Naas; Destouesse, Elodie; Lamminaho, Jani; Prete, Michela; Boukezzi, Larbi; Ebel, Thomas; Bessissa, Lakhdar; Rubahn, Horst-Günter; Turkovic, Vida; Madsen, Morten
Abstract : The development of nonfullerene acceptors (NFAs) has led to dramatic improvements in the device efficiencies of organic photovoltaic (OPV) cells. To date it is, however, still unclear how those laboratory‐scale efficiencies transfer to commercial modules, and how stable these devices will be when processed via industrially compatible methods. Herein, the degradation behavior of lab‐scale and scalable OPV devices using similar nonfullerene‐based active layers is assessed. It is demonstrated that the scalable NFA OPV exhibits completely reversible degradation when assessed in ISOS‐O‐1 outdoor conditions, which is in contrast to the laboratory‐scale devices assessed via the indoor ISOS‐L‐2 protocol. Results from transient photovoltage (TPV) indicate the presence of charge trap formation, and a number of potential mechanisms are proposed for the selective occurrence of this in laboratory‐scale devices tested in ISOS‐L laboratory conditions—ultimately concluding that it has its origins in the different device architectures used. The study points at the risk of assessing active layer stability from laboratory‐scale devices and degradation studies alone and highlights the importance of using a diverse range of testing conditions and ISOS protocols for such assessment. Abstract : The degradation behavior of nonfullerene organic solar cells developed from laboratory‐scale and scalable fabrication techniques is assessed, when aged using two different ISOS protocols. Outdoor experiments demonstrate a recovery effect not observed in laboratory studies. This highlights the importance of choosing suitable ISOS degradation conditions for assessing the desired application.